Effect of Moisture on the Orientation Birefringence of Cellulose Esters - Abd Manaf, Mohd Edeerozey; Tsuji, Manami; Nobukawa, Shogo; Yamaguchi, Masayuki (MDPI (Multidisciplinary Digital Publishing Institute), 2011)
Orientation birefringence and its wavelength dispersion are studied for hot-drawn films of cellulose esters such as cellulose triacetate (CTA), cellulose diacetate (CDA), and cellulose acetate propionate (CAP) exposed to three different humidities of environments. Hot-drawn CTA films show negative birefringence that decreases with increasing wavelength. On the other hand, CDA and CAP films show positive birefringence that increases with increasing wavelength, i.e., the so-called extraordinary wavelength dispersion of birefringence. Upon exposure to high humidity environment, the orientation birefringence of CDA and CAP decreases. The decrease is prominent for the samples containing a large amount of water. CTA, however, shows an increase in magnitude of its negative orientation birefringence with increasing moisture content. The results can be explained by the increase of the polarizability anisotropy perpendicular to the stretching direction in the cellulose esters. It is found from ATR-FTIR measurements that hydrogen bonds are formed between carbonyl groups of cellulose esters and water molecules. Considering that orientation birefringence of cellulose esters is determined mainly by ester groups, the formation of hydrogen bonds contributes to the polarizability anisotropy, thus affecting the orientation birefringence.